1991
DOI: 10.1007/bf02662155
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific analysis of triacyl‐sn‐glycerolsvia resolution of diastereomeric diacylglycerol derivatives by high‐performance liquid chromatography on silica

Abstract: and bKarlshamns LipidTeknik, S-104 65 Stockholm, Sweden 695The compositions of positions sn-1, 2 and 3 of triacylglycerols can be determined by partial hydrolysis with ethyl magnesium bromide, derivatization of the total products with (S)-(-F)-l-(1-naphthyl)ethyl isocyanate and isolation of the diacyl-sn-glycerol urethane derivatives by chromatography on solid-phase extraction columns containing an octadecylsilyl phase. The diastereomeric sn-l,2and 2,3-diacylglycerol derivatives are separated by highperformanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(80 citation statements)
references
References 15 publications
1
77
0
2
Order By: Relevance
“…Additionally, evening primrose oil and borage oil contain γ-linolenic acid (10.4 and 20.7%, respectively). A stereospecific analysis in edible plant oils showed that with some exceptions such as cocoa butter or peanut oil, unsaturated fatty acids are almost equally distributed in all positions of the glycerol skeleton (Brockerhoff and Yurkowski 1966;Christie et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, evening primrose oil and borage oil contain γ-linolenic acid (10.4 and 20.7%, respectively). A stereospecific analysis in edible plant oils showed that with some exceptions such as cocoa butter or peanut oil, unsaturated fatty acids are almost equally distributed in all positions of the glycerol skeleton (Brockerhoff and Yurkowski 1966;Christie et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Methanol, ethanol 99. 5 , potassium hydroxide, sodium methylate in methanol solution 28 , and other reagents were purchased from Kanto Chemical Co. Tokyo, Japan , Wako Pure Chemical Industries Osaka, Japan , and Nakalai Tesque Inc. Kyoto, Japan and were of analytical grades unless otherwise specified.…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…In addition to chemical 1,2 and NMR 3 methods, enzymatic methods to analyze the positional distributions of FAs in triacylglycerols TAGs have been developed since the 1960s 4 8 . These methods are based on selective hydrolysis of acyl groups at the 1 3 -position of TAGs using porcine pancreatic 4,5 or microbial lipases, such as Rhizopus oryzae lipase 6,7 . Although these methods have been applied to various vegetable and animal oils consisting mainly of C14-20 FAs, they are not suitable for TAGs containing short chain SC, C6 and polyunsaturated PU, C20 and 4 double bonds FAs.…”
Section: Introductionmentioning
confidence: 99%
“…This type of separation served as the basis for a novel procedure for stereospecific analysis of triacylsn-glycerols from natural oils and fats, i.e. for determining the compositions of fatty acids esterified to each of positions sn-1, sn-2 and sn-3 [37,38]. Triacyl-sn-glycerols were subjected to partial hydrolysis with a Grignard reagent and the p roducts we re conve rted to the (S) -( + ) -1 -( 1 -n ap h t hy l ) e t hy l urethane derivatives.…”
Section: Chiral High-performance Liquid Chromatographymentioning
confidence: 99%